PENGARUH KARAKTERISTIK TIM DAN KEADILAN KERJA TERHADAP KOMITMEN ORGANISASI PADA GURU SMA SWASTA KOTA BEKASI - Yasmin Faradiba (Jurnal Manajemen Pendidikan, 2013)
This research is aimed to investigate the effect of (1) team characteristis,, and (2) work justice toward (3) organizational commitment of teacher the private senior high school in Bekasi. In the data analysis, this research uses causal survey method by using Path Analysis Technique. This study uses the sample from 73 teachers in three private senior high school in Bekasi who are selected by using Slovin’fomula. The result of the study reveals that: Frist, there is a positive effect between team characteristics and teacher organizational commitment to the school. Second, there is a positive effect also between work justice and teacher organizational commitment to the school. Third, there is a positive effect between team characteristics and teacher organizationa’s commitment to the school.